The effect of educational models on learning some types of basketball scoring (Journal of the College of Basic Education, 2022)
The first chapter included the introduction and the importance of research in finding a new strategy in learning some types of basketball scoring. It is important to present a kind of modern strategies such as educational models supporting them with kinetic sentences. The research aimed to prepare educational units in the educational model according to the various kinetic sentences and learning some types of scoring. Basketball, and knowing the effect of the educational units and the educational model according to the various kinetic sentences in learning some types of basketball scoring. And to identify which of the two groups of the control and the experimental developed more according to the approach followed for the experimental group and the effect of the strategy of the educational models and kinetic sentences of the control groupThe second chapter included the research methodology and its field procedures, and the researcher used the experimental method in the style of equivalent experimental samples for the universe, and the research sample amounted to (60) students from the first stage students in the Department of Physical Education and Sports Sciences - University College of Peace for the academic year 2021/2022, and the sample percentage was (54%) of the original population, they were divided by the systematic random method into two groups (controller and experimental) with (35) students for each group. As for the experimental group, the educational units were applied according to the educational models using the various kinetic sentences, and it amounted to (16) educational units and two units Teaching per week, unit time (90) minutes. . The third chapter included presentation, analysis and discussion of the results, and included a detailed presentation of the results of all tests. The fourth chapter included the most important conclusions, which are the superiority of the experimental group to which the educational models were applied using various kinetic sentences over the control group that applied the curriculum followed by the subject teacher in learning some types of basketball scoring. The researcher recommends emphasizing the use of educational models in the lesson of physical education and sports sciences to learn some types of basketball scoring. It is better to include exercises that contain a variety of kinetic sentences in practical lessons to learn and improve the skill abilities of students with basketball through which the student masters more than one skill